A rare case of duodenal cancer with achalasia cardia - Mishra, Kartikesh (Journal of Society of Surgeons of Nepal, 2019)
Duodenal adenocarcinoma constitutes 0.4% of gastrointestinal malignancies. Achalasia incidence rate is 0.5-1.2 per 100000. The combination is rare.This is a report of a 68-year-old male from Nepal with history of five years abdominal pain, dysphasia and weight loss. Duodenoscopy could confirm ulcero-proliferative growth at D1-D2. Barium meal depicted features of achalasia cardia.No similar case report suggests that occurrence of duodenal carcinoma and achalasia cardia is merely co- incidental.Discussion: No similar case report suggests that occurrence of duodenal carcinoma and achalasia cardia is merely co- incidental.Consent: Informed consent was obtained from the patient for publication of this case report .